Guilty of everything - Armstrong, John 1956- (NEW STAR BOOKS, 2022)
"It's 1978 and a non-stop carnival of debauchery begins as the first shock of punk hits Vancouver. Now, in 2022, revisit John Armstrong's pivotal memoir in the 21st anniversary edition of Guilty of Everything. As Buck Cherry - lead singer and guitarist of The Modernettes - Armstrong had himself a front row seat to the frenzy of the 70s and 80s alongside the likes of I Braineater, Joey Shithead, Dimwit, Chuck Biscuits, Mary Jo Kopechne, Art Bergmann and other figures of Vancouver's earliest punk days. From White Rock to Vancouver, the back rooms and alleys of the Smilin' Buddha to the Commodore Ballroom, Guilty of Everything recounts the drug-addled, booze-soaked days and nights of this anarchic era, brought to life once again by Armstrong's candid and compelling prose."--
Keywords: Armstrong, John -- 1956-; Geschichte 1956-; Punk Rock; Rockmusiker; Kanada; Armstrong, John / 1956-; Punk rock musicians / Canada / Biography; Musiciens punk / Canada / Biographies; Punk rock musicians; Canada; autobiographies (literary works); Autobiographies; Biographies; Autobiografie